2017
DOI: 10.1071/py15187
|View full text |Cite
|
Sign up to set email alerts
|

Newly arrived refugee children with Helicobacter pylori are thinner than their non-infected counterparts

Abstract: The hypothesis of this study was that those refugee children with Helicobacter pylori are thinner than their non-infected counterparts. This cross-sectional study investigated the height and weight of newly arrived refugee children up to age 19 years, who were screened for H. pylori using a stool antigen test at the Migrant Health Service in Adelaide between August 2010 and October 2013. Of 460 children, 21% were infected with H. pylori. After adjusting for vitamin B12 and iron levels, ethnicity, age and sex, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Patients with non-GI related conditions, for example coronary heart disease ( Coles et al, 2003 ), diabetes ( Schimke et al, 2009 ), sudden infant death syndrome (SIDS) ( Ho et al, 2001 ), multiple sclerosis ( Pedrini et al, 2015 ) and HIV/AIDS ( Edwards et al, 1991 ) were also commonly investigated. Specific cultural groups studied included both urban and rural Aboriginal populations (8.0% of the included publications) ( Windsor et al, 2005 ; Dwyer et al, 1988b ; Pringle et al, 2015 ; Mollison et al, 1994 ; McDonald et al, 2004 ; Ritchie et al, 2009 ), newly arrived migrants (10.6% of included studies) ( Dwyer et al, 1988a ; Gibney et al, 2009 ; Chaves et al, 2009 ; Cherian et al, 2008 ; Mutch et al, 2012 ; Johnston, Smith & Roydhouse, 2012 ; Abdul Rahim et al, 2017 ; Benson, Rahim & Agrawal, 2017 ), ethnic groups such as members of the Chinese population of Melbourne (2.6% of included studies) ( Chow et al, 1995 ; Lin et al, 1991 ), and institutionalised populations (2.6% of included studies) ( Lambert et al, 1995 ; Wallace, Webb & Schluter, 2002 ). Several studies investigated groups of health professionals, hypothesised to be at greater risk of contracting H. pylori , including dentists ( Lin et al, 1998b ) gastroenterologists ( Lin et al, 1994 ) and nurses ( Robertson, Cade & Clancy, 1999 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with non-GI related conditions, for example coronary heart disease ( Coles et al, 2003 ), diabetes ( Schimke et al, 2009 ), sudden infant death syndrome (SIDS) ( Ho et al, 2001 ), multiple sclerosis ( Pedrini et al, 2015 ) and HIV/AIDS ( Edwards et al, 1991 ) were also commonly investigated. Specific cultural groups studied included both urban and rural Aboriginal populations (8.0% of the included publications) ( Windsor et al, 2005 ; Dwyer et al, 1988b ; Pringle et al, 2015 ; Mollison et al, 1994 ; McDonald et al, 2004 ; Ritchie et al, 2009 ), newly arrived migrants (10.6% of included studies) ( Dwyer et al, 1988a ; Gibney et al, 2009 ; Chaves et al, 2009 ; Cherian et al, 2008 ; Mutch et al, 2012 ; Johnston, Smith & Roydhouse, 2012 ; Abdul Rahim et al, 2017 ; Benson, Rahim & Agrawal, 2017 ), ethnic groups such as members of the Chinese population of Melbourne (2.6% of included studies) ( Chow et al, 1995 ; Lin et al, 1991 ), and institutionalised populations (2.6% of included studies) ( Lambert et al, 1995 ; Wallace, Webb & Schluter, 2002 ). Several studies investigated groups of health professionals, hypothesised to be at greater risk of contracting H. pylori , including dentists ( Lin et al, 1998b ) gastroenterologists ( Lin et al, 1994 ) and nurses ( Robertson, Cade & Clancy, 1999 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies investigated groups of health professionals, hypothesised to be at greater risk of contracting H. pylori , including dentists ( Lin et al, 1998b ) gastroenterologists ( Lin et al, 1994 ) and nurses ( Robertson, Cade & Clancy, 1999 ). Fourteen of the included papers (19%) estimated H. pylori prevalence in children ( Windsor et al, 2005 ; Moujaber et al, 2008 ; Dwyer et al, 1988a ; Dwyer et al, 1988b ; Mitchell et al, 1993a ; Hardikar et al, 1996 ; Hardikar et al, 1991 ; Mitchell et al, 1993b ; Hardikar & Grimwood, 1995 ; Ho et al, 2001 ; Ritchie et al, 2009 ; Cherian et al, 2008 ; Mutch et al, 2012 ; Benson, Rahim & Agrawal, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, other authors have noted that a positive association of H. pylori infection with BMI was only seen in those aged 15+ years [ 4 ]. Recently, Benson et al determined that the odds of being thin in the 10- to 19-year-old age group were 4.28-fold higher (95% CI 1.48–12.4) if they were H. pylori positive compared with those who were H. pylori negative [ 28 ]. In contrary, H. pylori infection was not associated with overweight/obesity observed from the retrospective study in this Chinese population [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, in one cross‐sectional study for H. pylori infection diagnosis, the exact same SAT (Guangzhou Wondfo Biotech, China) was used . One study using an SAT found it to be a cost‐effective and rapid method for initial screening of H. pylori infection …”
Section: Noninvasive Testsmentioning
confidence: 99%
“…30 One study using an SAT found it to be a costeffective and rapid method for initial screening of H. pylori infection. 31 Moon et al analyzed the relationship between the serum pepsinogen (PG) level and SAT in 318 H. pylori-seropositive patients.…”
Section: Stool Antigen Test (Sat)mentioning
confidence: 99%